Beneficial impact of exogenous arginine, cysteine and methionine on postharvest senescence of broccoli. (15th February 2021) - Sohail, Muhammad; Wills, R.B.H.; Bowyer, M.C.; Pristijono, Penta
Highlights: Arginine, cysteine and methionine dips equally inhibit broccoli senescence. Initial action of amino acids is to reduce ethylene production and respiration. Amino acids give marketing benefit through delayed loss of green colour in storage. Amino acids benefit vitamin C, weight loss, ion leakage, antioxidant & PAL activity. Abstract: This study examined the ability of l -arginine, l -cysteine and l -methionine, to inhibit postharvest senescence of broccoli. Florets were dipped in aqueous solutions of the amino acids at concentrations from 1.0 to 100 mM and stored at 10 °C. A 5 mM dip was found to be optimal in delaying senescence as measured by retention of green colour, vitamin C and antioxidant activity, and a lower level of ethylene production, respiration, weight loss, phenylalanine ammonia lyase (PAL) activity and ion leakage with the benefits being similar for all three amino acids. Arginine, cysteine and methionine have Generally Recognised As Safe (GRAS) status and should have few impediments in obtaining regulatory approval for commercial use if similar effects were found for other leafy vegetables.